Electrical conductivity investigation of a nonwoven fabric composed of carbon fibers and polypropylene/polyethylene core/sheath bicomponent fibers. (15th December 2016) - Lu, Longsheng; Xing, Di; Xie, Yingxi; Teh, Kwok Siong; Zhang, Bin; Chen, Songmao; Tang, Yong
Abstract: Carbon fiber (CF) nonwoven fabric, due to its mechanical robustness, compact structure and remarkable electrical properties, can be used as an electrode for energy storage devices and as a functional layer for electromagnetic interference (EMI) shielding equipment. To enhance the flexibility of CF nonwoven fabrics, a polypropylene/polyethylene (PP/PE) core/sheath bicomponent fiber (commercially known as PP/PE side by side fiber, simplified as ESF) was incorporated into the fabric to form a CF-ESFs composite. Using a two-step wet papermaking/thermal bonding process, we synthesized a highly flexible, and highly conductive nonwoven fabric, called CF-ESF nonwoven fabric (CEF-NF). Pure CF nonwoven fabrics and CEF-NFs were fully characterized via scanning electron microscopy, to understand and validate the improvement in tensile strength due to the incorporation of ESFs. The electrical conductivity of the CEF-NF was measured to elucidate the effect of heat pressing and to investigate its importance in enhancing the electrical conductivity of a CEF-NF. Lastly, we found the electrical conductivity of CEF-NFs increased with increasing fiber lengths and higher CF volume density. A theoretical model was established to express the relation between the electrical conductivity and CF concentration. From this model, we located the percolation threshold for the CF concentration of a CEF-NF. Graphical abstract: Highlights: Nonwoven fabrics composed of carbon fibers and polypropylene/polyethylene core/sheath bicomponent fibers were fabricated. Heat pressing process is a key step in determining the electrical conductivity of the novel nonwoven fabrics. The electrical conductivity of the novel nonwoven fabric increases as the carbon fiber length increases. The electrical conductivity in the novel nonwoven fabrics can be modeled by the percolation theory.